Inpatient forensic-psychiatric care: legal frameworks and service provision in three European countries - Edworthy, Rachel; Sampson, Stephanie; Völlm, Birgit (Elsevier, 2016)
Laws governing the detention and treatment of mentally disordered offenders (MDOs) vary widely across Europe, yet little information is available about the features of these laws and their comparative advantages and disadvantages. The purpose of this article is to compare the legal framework governing detention in forensic psychiatric care in three European countries with long established services for MDOs, England, Germany and the Netherlands. A literature review was conducted alongside consultation with experts from each country. We found that the three countries differ in several areas, including criteria for admission, review of detention, discharge process, the concept of criminal responsibility, service provision and treatment philosophy. Our findings suggest a profound difference in how each country relates to MDOs, with each approach contributing to different pathways and potentially different outcomes for the individual. Hopefully making these comparisons will stimulate debate and knowledge exchange on an international level to aid future research and the development of best practice in managing this population.